БЕРДАҚ ШЫҒАРМАЛАРЫ ТАРИЙХЫЙ-ЭТНОГРАФИЯЛЫҚ ДЕРЕК СЫПАТЫНДА - Баўетдинов, Р.А.; Ганиев, Т.С. (FAN va JAMIYAT, 2018)
The article is devoted to the study of the issues of using of the work «Shejire» (Pedigree) as one of the historical-ethnographic sources of the famous poet and thinker Berdakh The author gives the analysis to the historical data in the book and emphasizes their positive influence on the quality and effectiveness of the lesson.